Utility of sleep stage transitions in assessing sleep continuity. - Laffan, Alison; Caffo, Brian; Swihart, Bruce J; Punjabi, Naresh M (Sleep, 2010)
STUDY OBJECTIVES: Sleep continuity is commonly assessed with polysomnographic measures such as sleep efficiency, sleep stage percentages, and the arousal index. The aim of this study was to examine whether the transition rate between different sleep stages could be used as an index of sleep continuity to predict self-reported sleep quality independent of other commonly used metrics. DESIGN AND SETTING: Analysis of the Sleep Heart Health Study polysomnographic data. PARTICIPANTS: A community cohort. MEASUREMENTS AND RESULTS: Sleep recordings on 5,684 participants were deemed to be of sufficient quality to allow visual scoring of NREM and REM sleep. For each participant, we tabulated the frequency of transitions between wake, NREM sleep, and REM sleep. An overall transition rate was determined as the number of all transitions per hour sleep. Stage-specific transition rates between wake, NREM sleep, and REM sleep were also determined. A 5-point Likert scale was used to assess the subjective experience of restless and light sleep the morning after the sleep study. Multivariable regression models showed that a high overall sleep stage transition rate was associated with restless and light sleep independent of several covariates including total sleep time, percentages of sleep stages, wake time after sleep onset, and the arousal index. Compared to the lowest quartile of the overall transition rate (<7.76 events/h), the odds ratios for restless sleep were 1.27, 1.42, and 1.38, for the second (7.77-10.10 events/h), third (10.11-13.34 events/h), and fourth (≥13.35 events/h) quartiles, respectively. Analysis of stage-specific transition rates showed that transitions between wake and NREM sleep were also independently associated with restless and light sleep. CONCLUSIONS: Assessing overall and stage-specific transition rates provides a complementary approach for assessing sleep continuity. Incorporating such measures, along with conventional metrics, could yield useful insights into the significance of sleep continuity for clinical outcomes.
Keywords: Age Factors; Aged; Arousal; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Polysomnography; Predictive Value of Tests; Risk Factors; Sex Factors; Sleep Stages; Sleep Wake Disorders